Nietzsche: a noção de estímulo e a crítica do prazer e do desprazer como causas - Silva, Ricardo Rodrigo França da (2021)
The theme of this research is pleasure and displeasure in Nietzsche's philosophy. Its overall issue is to comprehend the theoretical role of pleasure and displeasure conceptions. For this endeavor, it is necessary to explain that Nietzsche considers pleasure and displeasure to be causes of actions, that is, man seeks pleasure and flees from displeasure. This idea appears in Human, all too Human I (1878), Human II (1879), and the Posthumous Fragments that preceded his elaboration, i.e. from 1877 to 1878. This search for pleasure and escape from displeasure, on the other hand, is experienced from two perspectives: that of the captive spirit, as discussed in the first chapter when emphasizing the moral context, and that of the free spirit, as discussed in the second chapter. It is proposed that Nietzsche gradually abandons the concept of pleasure and displeasure as the causes of actions when he introduces the concept of stimulus, which prepares the concept of impulse, on which the morphology and theory of the development of the will to power will be developed later. Thus, in a third instance, it is necessary to demonstrate how the concept of stimulus contributed to the critique of pleasure and displeasure as the causes of actions. To do so, Unpublished Fragments from 1880 to 1881, as well as other works related to those periods, as well as The Daybreak (1881) and The Gay Science (1882), are consulted, in which it is possible to verify the transition between pleasure and displeasure as a cause of actions and the transition to the conception that pleasure and displeasure are secondary phenomena, when considering the dynamics of external and internal stimuli and impulses to the organism.